Portal hypertensive colopathy in Egyptian cirrhotic patients: an endoscopic study - Helmy Shalaby; El-Sa; Sabry Al-Azhary; Khaled Nagy Elfayoumy; El-Sayed Abo Zeid (SpringerOpen, 2018)
Background Hepatitis C virus (HCV) infection is a major health problem in Egypt. It is often complicated by liver cirrhosis and portal hypertension, resulting in gastroesophageal varices, gastropathy, and colopathy. However, there is still lack of data with respect to the prevalence and clinical relevance of colopathy in this kind of liver disease. The aim of this study was to determine the prevalence of colopathic lesions in HCV-related cirrhotic patients, and to study their associations with the severity of liver disease and manifestations of portal hypertension Patients and methods This cross-sectional study included 60 patients with liver cirrhosis who were submitted to thorough clinical, laboratory, and ultrasonographic examinations. In addition, both upper and lower gastrointestinal endoscopy were performed to detect portal hypertensive complications including colopathic lesions. According to their severity, colopathic lesions were graded into three grades. Patients with higher colopathic grading (grade 2 and 3) were compared with the remaining participants with respect to the severity of the liver disease and other manifestations of portal hypertension. Results The prevalence of colopathy in cirrhotic patients with underlying HCV etiology was 91%. Patients with higher grades of colopathy were characterized by more severe liver disease. Moreover, they had increased frequency of both esophageal and gastric varices, and prior sclerotherapy or band ligation, as well as more collaterals and gastropathy, and higher grades of esophageal varices. Conclusion Colopathic lesions are frequent in patients with HCV-induced cirrhosis. Getting endoscopic treatment for varices is a risk factor for developing higher grades of colopathy. The latter could be considered as a marker of a worse prognosis in patients with HCV cirrhosis.